Historical Relationship with Adolescent Pregnancy Stunting Events in Children Age 24-60 Months in Pranggang Village, Kediri District - Suwoyo Suwoyo; Berty Pritasari; Indah Rahmaningtyas (Journal for Quality in Public Health, 2021)
Stunting is a condition where a toddler has less length or height when compared to age. Toddler stunting will have a level of intelligence that is not optimal, become more susceptible to disease and in the future, it can risk a decrease in the level of productivity which in the end, broadly stunting will be able to inhibit economic growth and increase poverty. The prevalence of stunting toddlers aged 0 to 59 months in East Java reached 32.81%. This figure is higher than the national stunting prevalence, which is 30.8%. The purpose of this study is to analyze the relationship between the history of teenage pregnancy with the incidence of stunting in children aged 24-60 months in Pranggang Kediri. Analytic survey research design with case-control survey design. The sampling technique uses Simple Random Sampling with a sample of 20 non-stunting toddlers and 19 stunting toddlers. The study was conducted in February-March 2020 in Pranggang Kediri. The analysis in this study used the Chi-square test with a significance level of 0.05. The research results showed a p-value (0.029) <0.05, which means there is a relationship between the history of teenage pregnancy with the incidence of stunting in children aged 24-60 months in Pranggang Kediri and the results of the contingency coefficient test of 0.337, it means there is a low relationship between the history of teenage pregnancy with the incidence of stunting in children aged 24-60 months in Pranggang Kediri. Based on the results of this study it is expected that there is an increase in maternal knowledge about factors related to the incidence of stunting.